APPROPRIATENESS OF POCKETBOOK (HANDOUT) USING BARCODE THEMED ENVIRONMENTAL POLLUTION TO TRAIN THE DIGITAL LITERATION OF VII JUNIOR HIGH SCHOOL - Putri Apriliyani; Siti Nurul Hidayati (PENSA: E-JURNAL PENDIDIKAN SAINS, 2020)
This study aims to describe the validity of a pocketbook (handout) using the barcode in environmental pollution to train the digital literacy for seventh-grade junior high school student. The feasibility of reviewed based on three aspects, that are validity, practicality, and effectiveness. The validity aspect is through the validation of two science lecturers and a science teacher. The practicality aspect is through the observation method of learning implementation and the student questionnaire response method. The effectiveness aspect with pretest-posstest based on digital literacy. The result of pocketbook (handout) using barcode validation show a very good category with 5 tendencies. The practical aspects of the learning process showed very good results for each meeting, while overall student response show of 97.5% with a category very good. The effectiveness in training digital literacy is through increasing N-Gain each student and every indicator of digital literacy. Relatively the average score of students in the pre-test was 39.06 while the post-test was 85.31 with N-Gain 0.66 in the medium category. The conclusion of this research produces a pocketbook (handout) using barcode feasible to train students' digital literacy on environmental pollution material.Keywords: pocket books, handouts, digital literacy.